A search for novel synergistic combinations against prevalent fungal phytopathogens - Young, Taran (2023)
With the global population rising, the emergence of new types or variants of crop pathogens (phytopathogens), and the increasing resistance of these organisms to current crop treatments, there is an urgent need to improve global food security. Each year, fungi destroy crops that could feed up to 600 million people annually. Wheat, the most widely grown crop worldwide, has the second highest yield of all crops, with a global production of 778.5 million metric tonnes in 2021/2022. Zymoseptoria tritici, a major pathogen of wheat, causes Septoria Tritici Blotch (STB). This organism is responsible for around 70% of annual fungicide usage in the EU and up to 20% of annual yield losses in the UK. Novel treatments involving synergistic combinations of inhibitory compounds could improve efficacy while decreasing cost and toxicity to both non-target organisms and the wider environment. In this thesis, novel synergistic combinations of agents, primarily targeting Z. tritici, were sought. The initial focus was on protein translation as a target. Specifically, it was hypothesised that pairs of agents disrupting the fidelity of protein translation could be effective at synergistically inhibiting phytopathogenic fungi. To examine this, rational combinations of compounds were tested against fungi of interest.